Intestinal Transplantation in a Country Without Home Parenteral Nutrition: The Largest Report from the Middle East - Hamed Nikoupour; Mohammad Bagher Khosravi; Pooya Vatankhah; Mojtaba Shafiekhani; Mojtaba Shafiekhani; Alireza Shamsaeefar; Peyman Arasteh; Mohammad Hossein Anbardar; Mohammad Hossein Eghbal; MohammadAli Sahmeddini; et al. (Turkish Journal of Gastroenterology, 2022)
Background: Many regions of the world, especially middle- and low-income countries, lack facilities for home parenteral nutrition and thus cannot follow existing guidelines for intestinal transplantation. Herein, we report our experiences with treatment protocols, intraoperative management, and early postoperative outcomes among patients undergoing either isolated intestinal transplantation or multivisceral transplantation in our center. Methods: During a 1-year period from March 2019 to March 2020, a total of 9 intestinal transplantations including 6 isolated intestinal transplantations and 3 multivisceral transplantations were performed in our center. We reported on donor selection strategies, surgical treatment, anesthesiology care and protocols for total parenteral nutrition, immunosuppression regimen, and pathology evaluation. Results: Mean (standard deviation) age of patients was 37.5 ± 12.5 years. The majority of patients were females (7/9). The median (interquartile range) waiting time for patients from diagnosis to transplantation was 79 (34, 164) days. Our 7-day survey of the amount of fluid therapy after transplantation revealed that the greatest need for fluid therapy was seen on the second postoperative day. After transplantation, 2 patients showed a total of 3 episodes of severe rejection, 1 of which was antibody-mediated. The 1-year survival was 66.6% and the 2-year survival was 44.5% in our study population. The median (interquartile range) time to death was 157 (26.5, 382) days. The most common cause of death was sepsis in our series (3/5). Conclusion: Acceptable outcomes can be obtained with intestinal transplantation in countries without home parenteral nutrition by application of specific treatment protocols. Cite this article as: Nikoupour H, Bagher Khosravi M, Vatankhah P, et al. Intestinal transplantation in a country without home parenteral nutrition: The largest report from the middle east. Turk J Gastroenterol. 2022;33(9):793-802.